Dispersión de semillas por murciélagos: su importancia en la conservación y regeneración del Bosque Tropical. - Galindo González, Jorge (Instituto de Ecología, A.C., 1998)
The aim of this work is to answer two basic questions (1) Do neoiropical frugivorous bats, as seed dispersers, contribute to tropical rain forest regeneration’ and (2) What oould be the ecological consequences if frugivoroiis bats disappear from the hurnid tropics pastures? I reviewed informalion on a) rnovement patteins, foraging and resouice utiliration by bats, b) seed dispersal by bats and seed shadows created by thern in the New World tropical rain forest, and c) compare species eaten by bats with seed rain and vegetation composition and stiucture under isolaled trees in pastures ftorn Los Tuxtlas, México. The foraging habits and distances achieved dunng nocturnal flights of some Phyllostomidae bats are 1-20 km depending on sfiecies ancJ environmental conditions. The main seeds dispersad by bats are: Brosimum alicastrum, Cecrapia sp., Eugenia sp., Ficus sp,. Piper sp,, Solanum sp. and Spondias sp. Most of them are very abundant in seed rain in pastures, I conclude that frugivorous bats are important agents in the regeneration of tfie tropical forest in and around abandonad pastures in Mexican tropics.